Effects of short vs. Long warm-up protocols on biomechanics and performance in a 50- m swimming trial - Gil Calvo, M.; Asensio Moreno, M.; Boullosa, D. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to compare the effect of two warm-up, protocols differing in volume, on biomechanical and performance parameters in a simulated 50m freestyle swimming trial. Twelve well-trained male swimmers of regional and national levels performed, in random order, two 50-m time trials on separate days, after a 600m, 12 min warm-up (Short Warm-Up, SWU) or a 1200m, 24 min warm-up (Long Warm-Up, LWU) protocols in random order. The results show that only the SWU warm-up protocol significantly improved swimming performance, although there is no difference between protocols in most kinematic parameters.